Contemporary Music Composition “Konfrontasi” | Komposisi Musik Kontemporer “Konfrontasi” - I Putu Riangga Budi Pramana; I Wayan Suharta (GHURNITA: Jurnal Seni Karawitan, 2021)
“Konfrontasi” composition is a musical composition that refers to a representation of one form of conflict, which describes an event in which one provokes an action or argument opposite from another person who is considered an opponent openly. In music, confrontation is likened to a word that describes the dynamic and disharmist movement of musical sentences. Confrontation is realized based on the continuity of Gong Kebyar's gamelan character as a revealing medium, namely dynamic characters. Confrontation is realized with the aim of enhancing the knowledge and expertise of stylists to build the ability to create contemporary compositions based on simple thinking on the relevance of the characteristics of ideas to the characteristics of Gong Kebyar. In realizing the composition of Confrontation, stylists use the method of creation of Panca Sthiti Ngawi Sani consisting of: Ngawirasa (Inspiration), Ngawacak (Exploration), Ngarancana (Conception), Ngawangun (Execution), and Ngebah (Presentation). Konfrontasi composition is presented as a contemporary composition with structural parts consisting of three parts with a focus on the concept of contrast and harmony. Contemporary composition is a musical composition that not only considers free without considering conventional provisions or forgetting tradition.